Effectiveness of Applied Behavior Analysis (ABA) with regard to tooth brushing in autistic children - Felicia Melati; Ratna Indriyanti; Arlette Suzy Setiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Children demonstrating autistic spectrum disorders tend to be uncooperative when receiving dental treatment. Actions as simple as brushing the teeth with a prophylactic brush can constitute complex processes for children with such conditions. Applied behavior analysis (ABA) can train children in new positive behavior and it is, therefore, anticipated that an ABA-based approach iscapable of influencing the behavior of individuals with autistic spectrum disorder. Purpose: This study aimed to assess the effectiveness of the ABA-based approach for autistic children during dental brushing procedures. Methods: The research constituted a quasiexperimental single subject investigation of children presenting autistic spectrum disorders who attended the Lembaga Pendidikan Autisma Prananda, Bandung. Potential changes in the behavior of subjects were monitored four times during treatment with a one-week interval between consultations. Those subjects satisfying the inclusion criteria consisted of 11 boys and 4 girls. The data analysis used in this study consisted of an ANOVA test and a non-parametric Kruskal-Wallis test with a p–value < 0.005. Results: Changes in scores between the initial and final consultations were statistically significant with a p-value (0.269) <0.05. Statistically significant differences existed between changes in the behavior of level 1 and level 2 autistic subjects. Conclusion: An ABA-based approach effectively changes the behavior of autistic children with regard to prophylactic brushing. Children with level 1 autistic spectrum disorder demonstrate greater capacity to follow instructions and consistently implement a prophylactic brushing technique.